Phosphorylation of myelin regulatory factor by PRKG2 mediates demyelination in Huntington's disease. (9th April 2020) - Yin, Peng; Liu, Qiong; Pan, Yongcheng; Yang, Weili; Yang, Su; Wei, Wenjie; Chen, Xingxing; Hong, Yan; Bai, Dazhang; Li, Xiao‐Jiang; Li, Shihua
Abstract: Demyelination is a common pathological feature of a large number of neurodegenerative diseases including multiple sclerosis and Huntington's disease (HD). Laquinimod (LAQ) has been found to have therapeutic effects on multiple sclerosis and HD. However, the mechanism underlying LAQ's therapeutic effects remains unknown. Using HD mice that selectively express mutant huntingtin in oligodendrocytes and show demyelination, we found that LAQ reduces the Ser259 phosphorylation on myelin regulatory factor (MYRF), an oligodendrocyte‐specific transcription factor promoting the expression of myelin‐associated genes. The reduced MYRF phosphorylation inhibits MYRF's binding to mutant huntingtin and increases the expression of myelin‐associated genes. We also found that PRKG2, a cGMP‐activated protein kinase subunit II, promotes the Ser259‐MYRF phosphorylation and that knocking down PRKG2 increased myelin‐associated protein's expression in HD mice. Our findings suggest that PRKG2‐regulated phosphorylation of MYRF is involved in demyelination and can serve as a potential therapeutic target for reducing demyelination. Synopsis: Laquinimod reduces Ser259 phosphorylation of myelin regulatory factor and its binding to mutant huntingtin, alleviating expression of myelin‐associated genes and demyelination caused by mutant huntingtin in oligodendrocytes. Laquinimod alleviates the phenotypes and pathology of HD mice expressing mutant HTT in oligodendrocytes. Laquinimod inhibits the interaction of mutant HTT with MYRF by reducing the phosphorylation of MYRF and restores the expression of myelin genes. Reducing the phosphorylation of MYRF by knocking down PRKG2 increases the expression of myelin genes in HD mice. Abstract : Laquinimod reduces Ser259 phosphorylation of myelin regulatory factor and its binding to mutant huntingtin, alleviating expression of myelin‐associated genes and demyelination caused by mutant huntingtin in oligodendrocytes.